Synthesis and initial pharmacology of dual-targeting ligands for putative complexes of integrin αVβ3 and PAR2. Issue 8 (9th July 2020) - Majewski, Mark W.; Gandhi, Disha M.; Holyst, Trudy; Wang, Zhengli; Hernandez, Irene; Rosas, Ricardo; Zhu, Jieqing; Weiler, Hartmut; Dockendorff, Chris
Abstract : The first examples of dual-targeting ligands for protease-activated receptors (PARs) and integrins are described, with potential anti-inflammatory applications. Abstract : Unpublished data from our labs led us to hypothesize that activated protein C (aPC) may initiate an anti-inflammatory signal in endothelial cells by modulating both the integrin αVβ3 and protease-activated receptor 2 (PAR2), which may exist in close proximity on the cellular surface. To test this hypothesis and to probe the possible inflammation-related pathway, we designed and synthesized dual-targeting ligands composed of modified versions of two αVβ3 ligands and two agonists of PAR2. These novel ligands were connected via copper-catalyzed alkyne–azide cycloadditions with polyethylene glycol (PEG) spacers of variable length. Initial in vitro pharmacology with EA.hy926 and HUVEC endothelial cells indicated that these ligands are effective binders of αVβ3 and potent agonists of PAR2. These were also used in preliminary studies investigating their effects on PAR2 signaling in the presence of inflammatory agents, and represent the first examples of ligands targeting both PARs and integrins, though concurrent binding to αVβ3 and PAR2 has not yet been demonstrated.